Auto-destruic?a?o e auto-exclusa?o: o suici?dio nas a?reas rurais no Rio Grande do Sul - Brasil - Rosa Mendes, Jussara Maria; Werlang, Rosangela (Corporación Universitaria Americana, 2014)
Abstract This paper deals with suicide in rural areas of Rio Grande do Sul, Brazil, considering the relation of this phenomenon with the advance of the capitalism in the countryside. This change has been creating new living and working styles and, besides, processes which lead to illness. Among these processes, suicide becomes a reality as a process of self-destruction and self-exclusion. These are sociopathology of the development which is created in demonstrations of mental illness, depression, and suicides, driven by a model of development imposed in the rural area through the economic incentive and, also, through all the economic speech carrying a project of hope. It is about the social and economic systems acting as generators of precariousness, human, familiar and psycho-philosophical costs, desocialization processes, self-generated alienation, and self-cleaving, showing that it is increasingly necessary to think about the relation between the social and the individual in life and death processes.  Resumo Este artigo trata da questa?o do suici?dio no meio rural no Rio Grande do Sul, Brasil, a partir da articulac?a?o deste feno?meno com o avanc?o capitalista no meio rural. Este u?ltimo tem produzido novas formas de vida e trabalho e, ademais, processos de adoecimento. Entre tais processos ganha corpo o suici?dio enquanto processo de autodestruic?a?o, de autoexclusa?o. Sa?o as sociopatologias do desenvolvimento que se constituem em manifestac?o?es de doenc?as mentais, depressa?o e suici?dios, alavancadas por um modelo de desenvolvimento imposto ao meio rural atrave?s da incitac?a?o econo?mica e, ademais, por todo um discurso econo?mico portador de um projeto de esperanc?a. E? o sistema social e econo?mico agindo enquanto gerador da precariedade, de custos humanos, familiares, psicofisiolo?gicos, de processos de dessocializac?a?o, de alienac?a?o autogerada, de clivagem de si apontando que se deve, cada vez mais, refletir sobre a relac?a?o entre o social e o individual nos processos de vida e morte.